Synthesis and electrochemical properties of spinel Li4Ti5O12-x Cl (x) anode materials for lithium-ion batteries - Huang, Yudai; Qi, Yanling; Jia, Dianzeng; Wang, Xingchao; Guo, Zaiping; Cho, Won Il (SPRINGER, 2012)
Li4Ti5O12-x Cl (x) (0 acurrency signaEurox acurrency signaEuro0.3) compounds were synthesized successfully via high temperature solid-state reaction. X-ray diffraction and scanning electron microscopy were used to characterize their structure and morphology. Cyclic voltammetry, electrochemical impedance spectroscopy, and charge/discharge cycling performance tests were used to characterize their electrochemical properties. The results showed that the Li4Ti5O12-x Cl (x) (0 acurrency signaEurox acurrency signaEuro0.3) compounds were well-crystallized pure spinel phase and that the grain sizes of the samples were about 3-8 mu m. The Li4Ti5O11.8Cl0.2 sample presented the best discharge capacity among all the samples and showed better reversibility and higher cyclic stability compared with pristine Li4Ti5O12. When the discharge rate was 0.5 C, the Li4Ti5O11.8Cl0.2 sample presented the superior discharge capacity of 148.7 mAh g(-1), while that of the pristine Li4Ti5O12 was 129.8 mAh g(-1); when the discharge rate was 2 C, the Li4Ti5O11.8Cl0.2 sample presented the discharge capacity of 120.7 mAh g(-1), while that of the pristine Li4Ti5O12 was only 89.8 mAh g(-1).
Keywords: ELECTRODE MATERIALS; COMPOSITE; DOPANT; CELLS; MG